The Quranic Model of Changing the Attitude or Correcting the Human Valuation - B.H. Husseini Dolatabad; Hasan Naqizadeh (آموزه‌های قرآنی)
Man constantly applies measures for the evaluation and valuation of the phenomena. The measures change under the effect of the different factors. Meanwhile, every person's facing and contact with the information and new phenomena relating to the process type and his conceptual system interaction causes a type of change in all his previous measures and values. It can be said that all person's relationship (ratios) has been reinvestigated and corrected by the new scale. But this current which is named the correction system of ratios in this paper is lasted till the person's scale completely coincides with the truth and reality. Of course, this conversion and relativity only occurs in the human nafs (self) ant not in the outward reality and the religious knowledge. The basis of changing the attitude and the scale of the man's valuation has been generally studied in the epistemology and ethics (or moral philosophy). But mostly it has not been mentioned how the epistemological system is. While investigating the contents of the Quran verse, This research has deduced the pillars and process for this system  and  shows  that  this  conversion  moves  through two ways progressive and unprogressive which it is affected by the divine and satanic strategies.